PENGARUH IMPLEMENTASI PRESENSI ONLINE (K-MOB) TERHADAP PENINGKATAN KEDISIPLINAN DAN KINERJA GURU SEKOLAH MENENGAH ATAS NEGERI (SMAN) DI KABUPATEN BOGOR - Supriyadi, Rena; Kartakusumah, Berliana; Luthfie, Muhammad (Administratie: Jurnal Administrasi Publik, 2021)
The level of discipline and quality of performance is an important factors in achieving organizational goals, a system or mechanism is needed in the framework of supervising the State Civil Apparatus (ASN) within the West Java Provincial Government, to realize this, the K-Mobile Online Presence application (K-Mob) was launched. in April 2019. The purpose of this study was to analyze how much influence the implementation of online attendance (K-Mob) had on improving the discipline and performance of high school teachers in Bogor Regency and to determine whether or not there was such an influence. This study uses a quantitative approach; the two variables studied, the independent variable and the dependent variable, are discussed, and then explained how the two are related or have an impact. The results showed that the implementation of K-Mob online presence improved the discipline and performance of SMAN teachers in Bogor Regency and that the effect of implementing K-Mob online attendance on SMAN teacher discipline was greater than the performance of SMAN teachers.